Practitioners’ and researchers’ perspectives on treatment needs and service provision for online child sexual abuse - Schmidt, Felipa; Quayle, Ethel; Bucci, Sandra (Frontiers in Psychology, 2025)
Online child sexual abuse (OCSA) presents unique and evolving challenges for young people and those supporting them. Although the long-term psychological impacts of OCSA are increasingly recognized, there remains limited guidance for practitioners on how best to assess and respond effectively to its specific features. This study aimed to explore practitioners’ and researchers’ perspectives on current gaps in service provision, assessment practices, and interventions for young people affected by OCSA. An open-ended online questionnaire was emailed to UK-based practitioners (n = 10) and researchers with published expertise in OCSA (n = 36), of whom seven also had clinical experience (i.e., clinical psychologists, psychiatrists). A total of 46 responses were analyzed using thematic content analysis. Most participants defined OCSA broadly as ‘any sexually abusive act by an adult or peer with a digital or online component’. Both practitioners and researchers emphasized the need for responses that include psychoeducation, trauma-informed care, and safeguarding measures. Participants also highlighted challenges unique to OCSA, such as the permanence of abuse imagery and the perceived agency of victims in online interactions, factors which were seen to require specialized responses. Despite these needs, both groups highlighted gaps in specialist support, practitioner training, and co-ordinated multi-agency responses. The findings highlight the urgent need for further research to develop consensus-based, evidence-informed approaches to OCSA-specific assessment and intervention, ensuring services are equipped to meet the needs of this vulnerable population.